2018
DOI: 10.1128/jcm.01523-17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of SensiTest Colistin, a Broth Microdilution-Based Method To Evaluate Colistin MICs

Abstract: The global spread of multidrug-resistant Gram-negative bacteria has led to the return of colistin for treating severe infections. Recently, different plasmid-mediated genes conferring resistance to this drug were described and reported worldwide. International committees (EUCAST/CLSI) reevaluated inconsistencies surrounding colistin antimicrobial susceptibility testing (AST), concluding that broth microdilution (BMD) should serve as the reference method for AST. The development of an accurate, reproducible com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
(15 reference statements)
2
36
0
1
Order By: Relevance
“…The MICRONAUT‐S system was shown to have the same EA as Sensititre, albeit it had lower CA (89%) and higher ME (15.38%) and VME (5.56%) (Table )(Matuschek et al., ). It can be observed from Table that Vitek had the poorest sensitivity (42.9%) to mcr‐1 producers and highest VME (36%) among all the commercial systems, which has also been confirmed by BioMerieux (Carretto et al., ). Moreover, it has been already reported that the Vitek 2 has poor sensitivity in detecting heteroresistance (Jayol, Nordmann, Brink, et al., ; Jayol, Nordmann, Lehours, et al., ).…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…The MICRONAUT‐S system was shown to have the same EA as Sensititre, albeit it had lower CA (89%) and higher ME (15.38%) and VME (5.56%) (Table )(Matuschek et al., ). It can be observed from Table that Vitek had the poorest sensitivity (42.9%) to mcr‐1 producers and highest VME (36%) among all the commercial systems, which has also been confirmed by BioMerieux (Carretto et al., ). Moreover, it has been already reported that the Vitek 2 has poor sensitivity in detecting heteroresistance (Jayol, Nordmann, Brink, et al., ; Jayol, Nordmann, Lehours, et al., ).…”
Section: Resultsmentioning
confidence: 55%
“…The MICRONAUT MIC‐Strip (MMS) (MERLIN Diagnostika Gmbh, Bornheim, Germany), the UMIC system (Biocentric, Bandol, France), the MIC Test Strip (MTS) (Liofilchem, Roseto degli Abruzzi, Italy) and Sensitest Colistin (Liofilchem, Roseto degli Abruzzi, Italy) (Carretto et al., ) are novel commercial but manual tests (Table ). E ‐test and BMD, which are older MIC‐determining methods, were evaluated by two and single studies, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations